COLD AGGLUTININ PADA PENDERITA COMMUNITY ACQUIRED PNEUMONIA - Johanis Johanis; Juli Soemarsono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Cold agglutinins at below physiologic body temperature can cause spontaneous agglutinations of erythrocytes. Cold agglutinins result from a particular antibodies activation on erythrocytes associated with a primary disease, including infection. The generation of antibody activates complement resulting in hemolysis. A 63-year-old man suffered from shortness of breath accompanied with productive cough, fever, right chest pain, loss of appetite, nausea, and occasionally vomiting. Physical examination showed an increase of pulse rate, respiration rate, and body temperature. Lung examination showed right intercostals retraction and rales in both lungs, but no abnormality detected in other organs. Chest X-ray showed pneumonia. EDTA whole blood showed spontaneous agglutinations at room temperature, however this did not occur by maintaining temperature at 37° C. Different complete blood count results were shown between agglutinated blood and absent of agglutination blood samples. As anti-I, anti-i, and/or anti-H was suspected, agglutinations for anti-A and anti-AB occurred by using ABO forward grouping test, whereas reverse grouping showed agglutinations for A, B, and O cells. Protein electrophoresis showed increase of alpha- 1 and gamma globulin; decrease of renal function; slightly increase of indirect bilirubin; and suspected Extended Spectrum Beta-Lactamase (ESBL) Klebsiella pneumoniae. The diagnosis of this case was community acquired pneumonia and suspected ESBL. Cold agglutinins affected CBC evaluations mostly shown in the erithrocyte index, nevertheless this could prevented by maintaining at physiologic body temperature. Infection could induce activation of cold agglutinins.